Biomarkers after pediatric heart surgery - (:unkn) unknown (Springer International Publishing, 2015)
Pediatric heart surgery causes extensive neurological and myocardial injury and important inflammatory consequences. Adult survivors of CHD display late consequences of pediatric heart surgery. From a socioeconomical standpoint, congenital heart defects still have a significant impact on morbidity, mortality, and healthcare costs. In particular, neonates (0-30 days) have the highest mortality rate of 10.2 % compared to all other age groups. The most common cause of infant death in relation to birth defects is congenital cardiovascular defects, accounting for 24 %. Children with congenital heart disease are a growing group in the current era that require advanced monitoring. Novel biomarkers can predict adverse long-term outcomes and guide management of critically ill patients. Children with congenital heart disease surely require advanced critical care and close monitoring after surgery, yet to a large extent, important indicators of clinical outcome such as biomarkers are not utilized in their care. Translational research can elucidate the utility of individual and interacting biomarkers after pediatric heart surgery. In addition to the traditionally studied biomarkers, novel biomarkers can help the clinician to identify children at high risk following pediatric heart surgery. Carefully designed studies can then compare biomarkers levels for comparison of pulsatile vs. non-pulsatile CPB and other neuro- or myocardial protective strategies. We need long-term follow-up studies to determine the relationship between novel biomarkers and neurological and cardiovascular outcomes after pediatric heart surgery. © Springer Science+Business Media Dordrecht 2015. All rights reserved.